1999
DOI: 10.1046/j.1365-2796.1999.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: a follow‐up study of the relation between the degree of right ventricle overload and the extent of perfusion defects

Abstract: Abstract. Ribeiro A, Lindmarker P, Johnsson H, Juhlin-Dannfelt A, Jorfeldt L (Karolinska Hospital, Karolinska Institute, Stockholm, Sweden). Pulmonary embolism: a follow-up study of the relation between the degree of right ventricle overload and the extent of perfusion defects. J Intern Med 1999; 245: 601]610.Objectives. To describe the course of changes in perfusion lung scintigraphy (LS) after acute pulmonary embolism (PE) and test the hypothesis that patients with persistent pulmonary hypertension (PH)/righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…The likely explanation may lie in the fact that ageing leads to degenerative involutional changes of the vessel walls and of the endothelium in the pulmonary bloodstream, resulting in lower production of vasodilating agents such as prostaglandins and nitrous oxide. Greater PE severity (in our patient group, intermediate or high risk PE) was proved to be a significant risk factor in several studies 7,12 and is related to the fact that clinically more serious PEs are associated with a greater degree of obstruction of the pulmonary bloodstream, which is in itself a well-known predictor of perfusion disorders 6,9 . In our study, interestingly, we found that increased hemoglobin levels are another significant risk factor of incomplete reperfusion.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…The likely explanation may lie in the fact that ageing leads to degenerative involutional changes of the vessel walls and of the endothelium in the pulmonary bloodstream, resulting in lower production of vasodilating agents such as prostaglandins and nitrous oxide. Greater PE severity (in our patient group, intermediate or high risk PE) was proved to be a significant risk factor in several studies 7,12 and is related to the fact that clinically more serious PEs are associated with a greater degree of obstruction of the pulmonary bloodstream, which is in itself a well-known predictor of perfusion disorders 6,9 . In our study, interestingly, we found that increased hemoglobin levels are another significant risk factor of incomplete reperfusion.…”
Section: Discussionmentioning
confidence: 63%
“…The reported rate of complete reperfusion 6-12 months after PE ranges from 33 to 81%, absence of any reperfusion is found in 3-16% (ref. 6,7,11 ). The wide range of results may be due to methodological issues -different patient classification, study period or different diagnostic methods (CT AG or VP scintigraphy).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations